PEMBUATAN PROGRAM APLIKASI GEREJA KRISTEN KALAM KUDUS - Henry Surya Wijaya (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
At this time the information is growing rapidly. dissemination of information is not only done through radio or newspaper but also has made use of the internet in the form of a website. website consists of static websites and dynamic websites. static website is a website that the contents of its website rarely make changes, while dynamic website is a website that the content of the website is always changing.To make a template in website requires the Dreamweaver aplication, to save the database requires mysql and to connect between mysql and localhost requires XAMPP application. The methodology used in this application is a program making Prototyping Methodology.  Key wordsWebsite, Mysql, XAMPP, Prototyping Methodology